PERAN KOMUNIKASI ISLAM DALAM KEHIDUPAN KELUARGA DAN MASYARAKAT INDONESIA DI ERA DISRUPSI - Abdul Basit (Hujjah: Jurnal Ilmiah Komunikasi dan Penyiaran Islam, 2020)
The current era of disruption has changed human life, including family life and Indonesian society. Facing this disruptive era requires a strong mind set and mentality so that tune in to life. One of the efforts that can be done by strengthening the role of Islamic communication in family and society life. Islam as the religion of the Indonesia's population majority has a significant role in changing family and society life. Islam as a source of values and ideology for the people has its own paradigm in developing communication. Therefore, this paper will describe the role of Islamic communication in family life and Indonesian society in the era of disruption. The author describes and analyzes data based on direct experience, field observations, and research results from scientists that are relevant to the main themes in this paper.